Mediating Food Sovereign Voices in Documentary Media - Khan, Sabiha Ahmad (Frontiers in Communication, 2020)
The aims of food sovereignty need to be underscored to counteract the prevalence of food insecurity media discourse during the COVID-19 pandemic. La Via Campesina’s inclusion of interacting with others in their definition of food sovereignty helps sustain food autonomy through shared food practices among populations deemed to be at risk. Key to sustaining autonomy is a revision of how food sovereign voices are mediated in documentary media. Documentary media often claim to amplify the voices of the powerless, a move that rings of the same type of paternalism that often marks food insecurity discourse. Drawing from currents in rhetorical studies, film studies, and studies in food communication, as well as my own documentary work, I argue that voice inheres in that which grates against a neoliberal understanding of food systems and the representational modes that operate within that sphere. Developing a documentary approach that navigates the modalities of mainstream food systems discourse while underscoring long-standing interactions of marginalized people around food is key to mediating food sovereign voices across cultures, generations, and palates.